2010
DOI: 10.4028/www.scientific.net/amr.152-153.1333
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Antibacterial Chitosan/Poly (Vinyl Alcohol) Nanofibers Containing Silver Nanoparticles

Abstract: New chitosan/poly (vinyl alcohol) (PVA) nanofibers functionalized with silver nanoparticles were electrospun using solutions of PVA blended with silver nanoparticles-chitosan composites. The structure of the electrospun fibers were studied with the aid of scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The results indicated that the electrospun fibers smoothly with 220 to 650 nm diameter, and the silver nanoparticles were successfully embed into the fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Of course this kind of data on the chelating capacity of nanofibrous mats endowed with large surface area can be extended to the enhancement of the antibacterial activity of silver chelates of this kind. In fact, electrospun chitosan + poly(vinyl alcohol) nanofibers functionalized with silver nanoparticles had 220–650 nm diameter, and the silver nanoparticles embedded into the fibers exerted high antibacterial activity against E. coli [ 81 ]. Data assessing the doping effects of monovalent, bivalent and trivalent metal ions on the morphological appearance of the electrospun chitosan + poly(ethylene oxide) blend nanofibers were made available by Su et al [ 82 ].…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…Of course this kind of data on the chelating capacity of nanofibrous mats endowed with large surface area can be extended to the enhancement of the antibacterial activity of silver chelates of this kind. In fact, electrospun chitosan + poly(vinyl alcohol) nanofibers functionalized with silver nanoparticles had 220–650 nm diameter, and the silver nanoparticles embedded into the fibers exerted high antibacterial activity against E. coli [ 81 ]. Data assessing the doping effects of monovalent, bivalent and trivalent metal ions on the morphological appearance of the electrospun chitosan + poly(ethylene oxide) blend nanofibers were made available by Su et al [ 82 ].…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…At present, there is no efficient usage of nanosilver for nanofiber mats, especially for sericin nanofiber mats. Mixing the nanosilver with the polymer solution prior to electrospinning is a general technique for nanofiber mats, as many studies have demonstrated favorable results in various nanofiber mats [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%